Trichoderma SPP : a biocontrol agent for sustainable management of plant diseases - Laila Naher; Umi Kalsom Yusof; Ahmad Ismail; Kausar Hossain (2014)
Trichoderma spp. are mainly asexual fungi that are present in all types of agricultural soils and also in decaying wood. The antagonistic activity of Trichoderma species showed that it is parasitic on many soil-borne and foliage pathogens. The fungus is also a decomposer of cellulosic waste materials. Recent discoveries show that the fungi not only act as biocontrol agents, but also stimulate plant resistance, and plant growth and development resulting in an increase in crop production. The biocontrol activity involving mycoparasitism, antibiotics and competition for nutrients, also induces defence responses or systemic resistance responses in plants. These responses are an important part of Trichoderma in biocontrol program. Currently, Trichoderma spp., is being used to control plant diseases in sustainable diseases management systems. This paper reviews the published information on Trichoderma spp., and its biocontrol activity in sustainable disease management programs.